Tuning Dzyaloshinskii–Moriya interaction via an electric field at the Co/h-BN interface. Issue 39 (29th September 2021) - Huang, C.; Jiang, L. Z.; Zhu, Y.; Pan, Y. F.; Fan, J. Y.; Ma, C. L.; Hu, J.; Shi, D. N.
Abstract : In this paper we found that the Dzyaloshinskii–Moriya interaction (DMI) at the Co/h-BN interface can emerge and is enhanced via applying a downward electric field. Abstract : The Dzyaloshinsky–Moriya interaction (DMI) at the Co/h-BN interface can emerge and be enhanced by applying a downward electric field. The height of the Co atom relative to the h-BN layer with the electric field determines the variation of DMI. One half reduction of J 1 is beneficial to generate skyrmions. Tuning the DMI by an electric field sheds new light for research on skyrmions.